Qualidade de vida familiar e necessidades de apoio de famílias de crianças e adolescentes com deficiências - Luiz, Érika de Aquino Marques (2019)
Deficiencies bring harm to the overall development of the individual; In this context, the family becomes the main support for children with disabilities, assuming the role of caregiver. The caregiver is required to participate less and less in activities for themselves, being involved in the routine of care, without valuing their own demands and their quality of life. For this reason, it is important to identify the needs of families and their demands to enhance the care and quality of life of caregivers. Thus, this study had the objective of knowing the support needs and the quality of life of the families of children / adolescents with disabilities in the municipalities of the State of São Paulo and to identify if the needs and quality of family life influence each other and if they are influenced by age, type of disability, severity of disability, family income and family composition. It is a cross-sectional, descriptive, comparative and correlational study, with a quantitative approach. Families of children and adolescents aged 0 to 17 years, 11 months and 29 days with disabilities were recruited by non-probabilistic sampling of convenience in municipalities of the State of São Paulo. As instruments were used: a questionnaire of general information about the person with disability and the family; "Family Needs Assessment" (ANF); and the Family Life Quality Assessment Questionnaire (QQVdF). The data collection was performed using the instrument self-application method, in places that provide care to children and adolescents with disabilities in municipalities of the State of São Paulo. To evaluate the data, we used simple percentages and frequencies, the Spearman correlation test and the chi-square test. The analyzes were carried out in environment R version 3.5.1. A total of 100 families of children / adolescents with disabilities participated in this study. Among the family members who answered the questionnaires, 85% were mothers, 11% were fathers and 4% grandparents, 96% of them were primary caregivers of children and adolescents with disabilities, of whom all mothers are included. Most families showed average levels of support needs, and were indifferent when their quality of life, that is, they are not satisfied or dissatisfied with it. It was possible to observe a moderate inverse correlation between the levels of support needs and the levels of satisfaction with the quality of family life. It was also possible to verify that there is an influence of the type and severity of the disability in the level of need of support and the quality life is influenced by family composition. The present study showed that families have moderate levels of support needs, and the main ones are related to therapies and physicians specific to their children's needs, appropriate educational services for them; they also have financial demands and emotional support, as well as to plan for the future when the family can no longer offer care. Families point out these needs as priorities, as well as promoting greater independence for their children with disabilities in day-to-day activities. The results also showed that the majority of families are indifferent to family quality of life. The highest levels of satisfaction are linked to the relationships they have with the professionals who attend them and with the members of their family. However, they are more dissatisfied with foreign aid to care for their children with disabilities, over time they are dedicated to individual interests, security and economic issues.